Duane Hanson : More Than Reality - Buchsteiner, Thomas; Schirn Kunsthalle Frankfurt; Galerie der Stadt Stuttgart; Padiglione d'Arte Contemporanea, Milano; Kunsthalle Rotterdam, Rotterdam; Scottish National Gallery of Modern Art, Edinburgh; Kunsthaus Zürich; Letze, Otto (Ostfildern-Ruit : Hatje Cantz Verlag Ostfildern-Ruit, 2001)
There are three observations that I would make about my work. First of all, and above all, I'm a sculptor, my most important concern is to get all the forms to look right. I try to eliminate faulty distortions and areas that look too flat, and those that do not register properly to my eye. Then, there is the matter of impact. I use models, oftentimes to get a maximum impact with the work, who are physically large and (to me) very sculptural, the third is one of communicating, this often takes care of itself. I express my feelings of empathy and sympathy for the subjects I portray through their weariness and despair. Duane Hanson
Duane Hanson Catalogue Reisonné p. 161-183
bibliog. (books, exhibition catalogues) p. 184-185, (articles) p. 186-189
Duane Hanson : More Than Reality, Schirn Kunsthalle Frankfurt, Frankfurt, 15/09/2001 - 06/01/2002 / Galerie der Stadt Stuttgart, Stuttgart, 19/01 - 28/04/2002 / Padiglione d'Arte Contemporanea, Milano, 29/05 - 01/09/2002 / Kunsthalle Rotterdam, Rotterdam, 14/09 - 24/11/2002 / Scottish National Gallery of Modern Art Edinburgh, Edinburgh, 14/12/2002 - 23/02/2003 / Kunsthaus Zürich, Zürich, 22/03 - 13/07/2003
Engels
boek
Keywords: Hanson, Duane